COVID-19 in Emerging Countries and Students’ Intention to Use Cloud Classroom: Evidence from Thailand - Singha Chaveesuk; Wornchanok Chaiyasoonthorn (Education Research International, 2022)
In many emerging markets, collectivist culture promotes interpersonal relationships which entail sharing both work and personal lives with one other. Nevertheless, the ubiquity of the World Wide Web has provided massive opportunities to teachers and learners around the globe to share knowledge anytime anywhere via online education. It is against this background that this study explores the perceptions of IT students in adopting virtual learning system in higher education institutes in an emerging country context under the COVID-19. We extended Davis’s (1989) Technology Acceptance Model (TAM) and evaluated students’ intention to use cloud classroom. Data were obtained from the five universities IT students in Bangkok, Thailand. Using partial least square structure equation modeling (PLS-SEM), the data of 373 IT students were analyzed. The findings of the research show that all hypotheses were supported, except one that was related to the positive impact of perceived usefulness on students’ intention to use cloud classroom. The extended TAM model explains 51.6% variance to explain students’ intention to use cloud classroom. The result of this study has useful implications for educationists and strategists related to the effectiveness and usability of cloud classroom in higher education institutions.
Keywords: Technology Adoption and User Behaviour; Organizational and Employee Performance; Technology-Enhanced Education Studies